2017
DOI: 10.4251/wjgo.v9.i12.466
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-stroma ratio as prognostic factor for survival in rectal adenocarcinoma: A retrospective cohort study

Abstract: AIMTo evaluate the prognostic value of the tumor-stroma ratio (TSR) in rectal cancer.METHODSTSR was determined on hematoxylin and eosin stained histological sections of 154 patients treated for rectal adenocarcinoma without prior neoadjuvant treatment in the period 1996-2006 by two observers to assess reproducibility. Patients were categorized into three categories: TSR-high [carcinoma percentage (CP) ≥ 70%], TSR-intermediate (CP 40%, 50% and 60%) and TSR-low (CP ≤ 30%). The relation between categorized TSR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 20 publications
4
47
1
Order By: Relevance
“…An existing cohort of 154 patients [8] with rectal adenocarcinoma stages I-III was used. All patients received curative surgery in the period 1996-2006 at the Medisch Spectrum Twente hospital (The Netherlands).…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…An existing cohort of 154 patients [8] with rectal adenocarcinoma stages I-III was used. All patients received curative surgery in the period 1996-2006 at the Medisch Spectrum Twente hospital (The Netherlands).…”
Section: Patientsmentioning
confidence: 99%
“…Generally, TSR is an independent prognostic factor, where a high content of intratumoral stroma is associated with a poor prognosis. A number of previous studies showed promising results on the prognostic relevance of TSR in CRC [8][9][10][11][12]. Despite this evidence, there is no implementation in routine pathology reporting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TSR assessment is easy, quick and without additional costs. Previous research demonstrated the prognostic value of the TSR in different types of invasive solid tumors, including breast cancer . Most of these studies validated a worse prognosis for patients with stroma‐high tumors.…”
Section: Introductionmentioning
confidence: 96%
“…Further, CAFs directly initiate tumour cell invasion by supporting epithelial-to-mesenchymal transitions (21)(22)(23) and by altering the composition and mechanical properties of tumour extracellular matrix (ECM) (24)(25)(26)(27). As a result, patients with tumours characterized by high stromal content carry a worse prognosis in a multitude of solid tumours (28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%